Patterns of genetic diversity in vervet monkeys (Chlorocebus aethiops) from the south eastern regions of South Africa - Coetzer, W. G. (University of the Free State, 2012)
Vervet monkeys (Chlorocebus aethiops) are one of the most widely distributed primate species in Africa. The aim of this study was to determine the level of genetic differentiation among conspecific vervet monkey populations in the south-eastern regions of South Africa, as part of a bigger project to determine levels of differentiation across South Africa. For this purpose, samples were taken from four localities in the Free State Province (Soetdoring Nature Reserve (NR), Gariep Dam NR, Sandveld NR and the Parys area), four Eastern Cape locations (Tsolwana NR, Baviaanskloof NR, Shamwari Private Game Reserve (PGR) and the Nelson Mandela Metropolitan University (NMMU) campus, Port Elizabeth), three Kwa-Zulu Natal location (St. Lucia area) and one Limpopo Province locality. Genetic differentiation was quantified using sequence data from a portion of the mtDNA control region. Twelve Haplotypes were identified within the total sample group. The nucleotide diversity for each grouping was calculated over all loci. Nucleotide diversity ranged from 0 to 0.038% ±0.02. Haplotype frequencies distribution among samples was calculated. An analysis of Molecular Variance (AMOVA) test was conducted and population pairwise FST values were estimated. The AMOVA test revealed that the majority of the genetic diversity occurred among the different groups (52.5%), with only 4.9% of the variation found within populations. The populations were assigned to groups according to geographic origins. The pairwise analysis identified significant levels of genetic variation among populations, with an average FST value of 0.851. These haplotypes were found to coincide with the geographical borders of Provinces. A ML tree was constructed using the haplotype data, and results showed clustering corresponding to geographical borders. A phylogenetic network was constructed, and this showed clustering similar to that found with the ML tree analysis. According to these results it is clear that there is genetic structuring among vervet monkey populations in South Africa. This clustering of populations can be potentially explained by female philopatry and geographical barriers. Female philopatry is a well known occurrence amongst Cercopithecine primates. The occurrence of geographical barriers, such as rivers and mountains had influence on migration rates and genetic structuring. This clustering pattern observed with mtDNA analysis contradicts results from previous studies working with nuclear DNA markers. This can be caused by various factors. Except for female philopatry having an effect on mtDNA differentiation patterns, it should be noted that the faster evolutionary rate of mtDNA vs. nuclear DNA can also cause different genetic patterns. The effective population size of mtDNA is also four-fold smaller than that of nuclear genes, and will also cause skewed results when comparing mtDNA data with nuclear DNA data. No reliable recommendations can be made toward the release of rehabilitated vervet monkeys, as further analysis is needed. It is thus suggested to use both genetic markers in follow-up studies. An increase in sample size from a broader geographical range is also recommended. In addition to further work on patterns of genetic variation, the adaptive significance of observed genetic differences should also be investigated.

Blouape (Chlorocebus aethiops) is een van die mees wyd-verspeide primaat spesies in Afrika. Die doel van hierdie studie was om die vlak van genetiese differensiasie tussen blouaap bevolkings in die suidoostelike gebiede van Suid-Afrika te identifiseer. Hierdie studie vorm deel van 'n groter projek wat gefokus is op die genetiese variasie van blouape regoor Suid-Afrika. Biologiese monsters was versamel vanaf vier areas in die Vrystaat (Soetdoring Natuurreservaat (NR), die Gariep dam area, Sandveld NR en die Parys area), vier areas in die Oos-Kaap (Tsolwana NR, die Baviaanskloof area, Shamwarie Privaat Wildreservaat en die NMMU kampus, Port Elizabeth) en drie Kwa-Zulu Natal areas (Blythedale Beach, Thorny Park Estate en St. Lucia area). 'n Gedeelte van die mtDNS kontrole gebied was gebruik vir die analiese van genetiese variasie deur middel van ONS volgorde bepaling. "n Analiese van die Molekulêre Variasie (AMOVA) toets was gedoen en tussen-bevolking FST waardes was bepaal. Die AMOVA toets het gewys dat die meerderheid van die genetiese diversiteit tussen die verskillende groepe voorkom (52.47%) en dat net 4.87% van die diversiteit binne elke populasie voorkom. Die groepe was volgens hul geografiese oorsprong (provinsies) gegroepeer. Betekenisvolle variasie was tussen die bvolkings gevind, met 'n gemiddelde FST waarde van 0.851. Die nukleotied diversiteit was vir elke populasie bepaal en was tussen 0 tot 0.038% ±0.02. Haplotiepe frekwensie verspreiding was ook bepaal. Twaalf haplotiepes was tussen die totale proef groep gevind. Die haplotiepe groepering was in lyn met die geografiese grense van Suid-Afrika. "n ML filogenetiese boom was opgestel deur gebruik te maak van die bepaalde haplotiepe data. Hierdie resultate was meer en deels in lyn met die bogenoemde haplotiepe frekwensie data. Die konstruksie van "n haplotiep netwerk het die ML boom resultate ondersteun. Hierdie resultate wys na defnitiewe genetiese strukturering tussen die blouaap populasies in Suid-Afrika. Hierdie groeperings patrone kan deur twee hoof meganismes beskryf word, naamlik vroulike trop-gebondenheid (philopatry) en geografiese skeidings. Cercopithecine primate is bekend daarvoor dat vroulike individue gebondenheid tot hul trop van oorsprong toon. Die tempo van migrasie en genetiese strukturering kan ook deur geografiese skeidings, soos berge en riviere, beïnvloed word. Die groeperings patrone wat deur mtDNS analiese waargeneem was is teenstrydig met vorige werk wat op kern DNA gefokus het. Die vinniger evolusionêre tempo van mtDNS teenoor kern ONS kan ook 'n invloed op genetiese patrone hê. Die effektiewe bevolkingsgrootte van mtDNS is ook vier keer kleiner as dié van kern ONS, en kan oneweredige resultate verskaf indien mtDNS data met kern DNS data vergelyk word. Tot op datum kan geen betroubare aanbevelings ten opsige van die vrylating van gerehabiliteerde blouape dus gemaak word nie, aangesien verdere inligting benodig word. Dit word dus voorgestel dat altwee tipes genetiese merkers vir toekomstige studies gebruik word, asook 'n groter proef groep wat 'n groter geografiese gebied dek. Behalwe vir die addisionele werk wat op die patrone van genetiese variasie gedoen moet word, moet die adaptiewe betekenis van die waargenome genetiese variasie ook ondersoek word.
Dissertation (M.Sc. (Genetics))--University of the Free State, 2012
Keywords: Vervet monkey; Chlorocebus aethiops; Genetic differentiation; mtDNA; AMOVA; Female philopatry; Haplotype frequencies; Clustering; Control region; Monkeys -- South Africa -- Genetics; Cercopithecus aethiops -- South Africa -- Genetics